2021
DOI: 10.21037/tau-20-1118
|View full text |Cite
|
Sign up to set email alerts
|

Current treatment options for newly diagnosed metastatic hormone-sensitive prostate cancer—a narrative review

Abstract: Prostate cancer continues to be one of the most commonly diagnosed cancers in men globally and a leading cause of male cancer deaths. The landscape of metastatic hormone-sensitive prostate cancer has significantly changed over the past decade. For many years, androgen deprivation therapy alone through surgical or chemical castration was the mainstay of treatment yielding limited 5-year survival rates. New treatment approaches using Docetaxel chemotherapy or androgen receptor pathway inhibitors to intensify upf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Distant nodes seen on PSMA PET-CT was found to be the only statistically significant predictor of treatment progression. These findings could imply that the detection of distant nodes allowed intensification of upfront therapy (chemotherapy or ARPIs) which the literature shows has benefit [ 14 ]. Interestingly, a negative PSMA PET-CT was not a statistically significant predictor of no treatment progression which may indicate the non-visible micro-metastatic disease leading to treatment progression.…”
Section: Discussionmentioning
confidence: 99%
“…Distant nodes seen on PSMA PET-CT was found to be the only statistically significant predictor of treatment progression. These findings could imply that the detection of distant nodes allowed intensification of upfront therapy (chemotherapy or ARPIs) which the literature shows has benefit [ 14 ]. Interestingly, a negative PSMA PET-CT was not a statistically significant predictor of no treatment progression which may indicate the non-visible micro-metastatic disease leading to treatment progression.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a poly(adenosine diphosphate-ribose) polymerase (PARP) inhibitor (olaparib), a new radioactive drug (Lutetium-PSMA) and several new ARTAs demonstrated encouraging outcomes in clinical trials [ 10 14 ]. In addition, a substantial amount of research has shown that more intense treatment approaches, rather than castration only, during the early castration sensitive phase improve survival [ 15 ]. Nonetheless, real-world studies have shown that overall survival (OS) in the mCRPC setting remains limited to 31 months in treatment-naïve patients, and only one year in patients progressing on docetaxel [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Androgen receptor inhibitors have been investigated, refined, and innovated for prostate cancer treatment since the 1960 s [2,3]. The first generation, or 'vintage,' androgen receptor inhibitors include bicalutamide, flutamide, and nilutamide, and had limited efficacy because of their less potent competitive androgen receptor inhibition, explaining their potential to perform as agonists over time, explaining PSA decline upon drug withdrawal [3].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple mechanisms, including mutations in the androgen receptor gene mutation or amplification, overexpression of androgen receptor co-regulatory molecules, and splice variants, are believed to play a role in the castration resistance state [5]. Second-generation androgen receptor inhibitors competitively inhibit the androgen receptor itself, and thus prevent translocation of the androgen receptor complex inside the nucleus and prevent gene modification and the downstream impact of the androgen receptor complex [2]. Multiple clinical trials are in progress, which will evaluate the role of androgen receptor inhibitors in different clinical settings, in combination with other therapeutics, and in adjuvant or neoadjuvant settings.…”
Section: Introductionmentioning
confidence: 99%